Progress in 1,3-propanediol biosynthesis - Li, Boran; Gao, Wenyan; Pan, Yuanyuan; Yao, Yongpeng; Liu, Gang (Frontiers in Bioengineering and Biotechnology, 2024)
1,3-Propanediol (1,3-PDO) is one of the important organic chemical materials and is widely used in polyester synthesis, and it also shows great potential in medicine, cosmetics, resins, and biodegradable plastics. So far, 1,3-PDO mainly comes from chemical synthesis. However, the by-products and the side effects during chemical synthesis of 1,3-PDO bring about serious damage to the environment. In recent years, the biosynthetic pathway of 1,3-PDO has been elucidated in microorganisms. Under the action of glycerol dehydratase (GDHt) and propanediol oxidoreductase (PDOR), glycerol can be catalyzed to form 1,3-PDO through the reduction pathway. Compared to the chemical synthesis, the biosynthesis of 1,3-PDO is environmentally friendly but would face the problem of low production. To improve the yield, the native 1,3-PDO producing strains have been modified by genetic engineering, and the biosynthetic pathway has been reconstructed in the model microorganism, Escherichia coli. In this review, we summarize the research progress of the 1,3-PDO biosynthesis in microorganisms, and hopefully, it will provide reference for the renewable production of 1,3-PDO in industry.